Adherence to advance directives in critical care decision making: vignette study. Issue 7422 (30th October 2003) - Thompson, Trevor; Barbour, Rosaline; Schwartz, Lisa
Abstract: Objective To explore health professionals' decision making in a critical care scenario when there is an advance directive. Design Qualitative study. Setting Scotland. Participants Interviewees (n = 12) comprising general practitioners, hospital specialists, and nurses, and six focus groups (n = 34 participants) comprising general practitioners, geriatricians (consultants and specialist registrars), hospital nurses, and hospice nurses. Results When presented with an advance directive that applied to the same hypothetical scenario, health professionals came to divergent conclusions as to the "right thing to do." Arguments opposing treatment centred on the supremacy of autonomy as an ethical principle. Other arguments were that the decision to treat was consistent with the terms of the advance directive, or that, notwithstanding the advance directive, the patient's quality of life was sufficient to warrant treatment. Conclusion Advance directives are open to widely varying interpretation. Some of this variability is related to the ambiguity of the directive's terminology whereas some is related to the willingness of health professionals to make subjective value judgments concerning quality of life.